DEVELOPMENT OF TOROSIAJE VILLAGE AS A TOURISM DESTINATION - Laisa, Sri Lusiana M.; Rahmatiah; Mondong, Tonny Iskandar; Arrazaq, Naufal Raffi (CV. Fahr Publishing, 2025)
This study discusses Torosiaje Village in Pohuwato Regency, Gorontalo Province, as a unique and historic marine tourism destination. This village is inhabited by the Bajo Tribe community who live on the sea of Tomini Bay and have unique cultures and environments that make them different from other tourist villages. The background of this study is the need to explore the potential of villages based on local wisdom in supporting sustainable development and improving community welfare. The purpose of this study is to identify and describe the history, community life patterns, and marine and cultural tourism potential of Torosiaje Village, as well as to describe the active role of the community in developing the tourism village. Inhabited by the Bajo Tribe community, this village is known for its location above the sea and its preserved maritime cultural wealth. Using historical research methods, this study explores the origins, development, and tourism and economic potential of the village. The results of the study show that community life in harmony with the sea, natural beauty, and preservation of local culture make Torosiaje have a high tourist attraction. Community support for the development of tourism villages, coupled with the potential for ecotourism and local friendliness, are important capital to encourage sustainable economic growth in the region. The conclusion of this study is that Torosiaje Village has great potential to be developed as a model of tourism village based on local wisdom. Support from the community, preservation of culture and nature, and the involvement of various parties in development are the main factors in realizing a sustainable and competitive tourism village.